PARADOKS MANAJEMEN MUTU: STANDARISASI PENDIDIKAN DI INDONESIA - Taufiqur Rahman (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2012)
Standardized education is strategical step to prepare the young of nations to compete in globalized era. Quality management is an instrument to ensure the process and result of stardized education. Paradoxically the differences between philosophical roots imply or affect both the process and the results. ‘Managerialism’ traps in governing the school and physicological effects of standardized assessment cause psedue advancement in Indonesian education.